Bare undoped nontoxic carbon dots as a visible light photocatalyst for the degradation of methylene blue and congo red. (March 2023) - Abbasi, Ambreen; Abushad, M.; Khan, Arisha; Bhat, Zia ul Haq; Hanif, Summaiya; Shakir, Mohammad
Highlights: Bare undoped carbon dots synthesized from diammonium citrate. One step pyrolysis method employed for synthesis of carbon dots. Carbon dots exhibited no cytotoxicity towards HCT 116 human colon cancer cell line. Synthesized carbon dots are used as visible light photocatalyst for degradation of cationic methylene blue and anionic Congo red dyes. Abstract: Rampant discharge of industrial wastes containing non-biodegradable colored dyes to water bodies has prompted the development of an environment-friendly photocatalytic process using nontoxic, photostable water soluble photocatalyst. In this work, bare undoped carbon dots (CDots) based photocatalyst has been reported. The carbon dots were synthesized via the pyrolysis method using a single source, ammonium citrate; the reported carbon dots were characterized using HR-TEM, XRD, FTIR, XPS, Photoluminescence (P.L.), TGA, and UV–Vis spectroscopy. The catalytic behavior of the synthesized carbon dots was tested against two water-soluble industrial dyes (Methylene Blue (M.B.) and Congo Red (C.R.)). The synthesized carbon dots exhibited excellent photocatalytic activity under visible light irradiation facilitating 96% degradation of MB within 55 min and 98% degradation of C.R. within 60 min. A plausible mechanism for the photocatalytic degradation of studied dyes was proposed based on comprehensive active species trapping experiments. The photogenerated holes ( h + ) and superoxide radicals (O2 .− ) were the main active species responsible for the degradation of studied dyes. The kinetic studies revealed that the cationic methylene blue dye degradation by BUCDs followed the modified Freundlich kinetic model with rate constant 0.063 and anionic congo red dye depicted closed correlation with both parabolic diffusion model and modified Freundlich kinetic model with rate constants 0.256 and 0.196. The synthesized BUCDs showed no cytotoxicity in HCT human colon cancer cell lines, thus establishing their nontoxic nature. Graphical abstract: Image, graphical abstract